STEP-BY-STEP TESTING METHOD: JOINT ASSESSMENT OF THE TRAINING LEVEL AND THE COMPLEXITY OF ASSIGNMENT - Ekaterina P. Mochalina; Galina V. Ivankova; Oleg V. Tatarnikov; Irina N. Maslyakova (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
This paper presents an innovation approach to teaching by step-by-step testing method, which generates the complexity of the task,  depending on the student's level of knowledge. Also we want to generate the assessment of the level of knowledge that is independent of the initial test conditions. The result of this work is the recurrent testing methodology which allows to estimate the student’s level of OC and PC (means the series of coming one after the other tests, each of which takes into account previous results). The results of that part of the work were presented on the international conference "Education, science and economics at universities and schools. Integration to the international educational area" (Goris, Armenia, 2015). An important, or even can be said, the main aspect is to demonstrate that the developed methodology, regardless of the starting point (initial test) rapidly converges to the student's level of knowledge. To prove the fact the corresponding mathematical model of the process (serial testing) was built. Its convergence also was studied. For the practical application of the developed estimation model of OC and the PC the database of tests is forming. We think also about its technical support by developing appropriate software.